An Extensible Plugin for Integrating High-Performance Collision Detection Broad-Phase Algorithms into Unity - Feitosa, Raul Costa; Rodrigues, Maria Andréia Formico (Anais do Workshop sobre Engenharia de Software para Desenvolvimento de Jogos (SE4Games); 2025: Anais do I Workshop sobre Engenharia de Software para Desenvolvimento de Jogos, 2025)
This paper presents a plugin architecture for Unity to integrate and benchmark broad-phase collision detection algorithms. The solution connects high-performance C++ algorithms to Unity’s C# environment via an external dynamic-link library, allowing developers to test and compare different methods in interactive scenarios. We evaluated three integrated algorithms (Brute Force, Tracy, and KDTree) in tests with up to 1600 objects (uniform and assorted) across ten distinct simulation configurations, assessing both algorithmic performance and the integration bridge’s efficiency. Results show a stable architecture, validating the use of C++ DLLs for intensive tasks in Unity and providing a modular framework to extend its native physics capabilities.